The hydrothermal formation of sulphides and sulphosalts at low temperatures (< 100°) - Elhaddad, Mervet A.; Moh, Günter (Mineralogy and petrology, 1992)
The investigations reported are concerned with the synthesis of simple sulphides, Tl-bearing sulphosalts, and antimony-iron sulphides in aqueous environment using a combination of clay/dolomite or clay/quartz buffer at a temperature range of 85-90°C. Clay minerals as “catalyst” have been employed because their K+, Na+, Ca2+, etc. contents have to be substituted by cations of Fe, Cu, As, Sb, Tl, Bi, etc. After substitution, the saturated clay minerals were in turn treated by aqueous H2S solution under controlled Eh-pH condition, where the heavy elements were extracted and precipitated as sulphide minerals.
Gesehen am 03.04.2023